Identiti Korporat Pemahaman dan Amalan dalam Kalangan Industri Perhotelan di Negeri Kedah - Nurul Husna, Akhmar (2011)
Corporate identity is an important element not only to the private organizations but also government sectors. Through corporate identity, any organizations can easily be known by the public. The study was conducted to understand, develop and practice corporate identity among the hotel industry in the state of Kedah. It uses qualitative methods and data was obtained through interviews and was analyzed using qualitative data analysis software NVivo version 8. The respondents of this study were from four different hotels in Kedah state and each hotel was represented by an officer who has been selected by the management of the hotel itself. The findings showed that there were similarities between the understanding of corporate identity practitioners in Kedah hotels and Western scholars. In the aspect of the corporate identity formation, all the elements specified by the respondent has been discussed by the researchers in previous studies. In corporate identity practice, there were various ways used by the hotel to show their corporate identities and some of the ways has been discussed by scholars in their research. This study also found a new element that has not yet been discussed by other researchers. Therefore, the findings of this study managed to enlighten and provide useful information about corporate identity in the organization to the various parties especially among the hotel industry in the state of Kedah.